Comparative evaluation of preparations’ fungicidal activity and their effect on pathogenic micromycetes of spring wheat - Ualiyeva, R.M. (Fundamental and Experimental Biology, 2023)
The growing season of 2022 was characterised by a variety of weather conditions, some of which were unfavourable to spring wheat growth and development. Plants were stressed by daytime temperatures, soil and air moisture, and fungal disease pathogenic impacts. Spring wheat was infected with powdery mildew (Erysiphe graminis), leaf brown rust (Puccinia triticina), and septoria leaf blotch (Septoria sp.). The main fertilizer, foliar dressing, and compounds with regulatory properties in relation to the crop are used to boost yield and improve grain quality. Fungicides such as Varro, Rex Duo and Kolosal Pro are effective for managing spring wheat diseases. The study established the impact of Varro, Rex Duo, and Kolosal Pro fungicides on the reduction of the main spring wheat pathogens. This had an effect on grain quality and yield characteristics. The fungicides (tested under stressful conditions produced by phytopathogens and unfavourable meteorological conditions) enhanced the growth of spring wheat plants and positively influenced yield morphometric parameters, productivity, and grain quality parameters. The most effective agent for controlling diseases of spring wheat is Rex Duo fungicide. The use of fungicidal treatments in combination with fertilizers and plant growth regulators increased yield structure indicators, which resulted in an even greater impact on yield and quality indexes. It was discovered that the use of fertilizers and growth stimulants to crops can be combined with the application of fungicides.